LITERATURE STUDY: TEACHING FACTORY IMPLEMENTATION ANALYSIS IN THE WORLD OF VOCATIONAL EDUCATION IN INDONESIA AS AN EFFORT TO FACE FUTURE CHALLENGES - Safarinah, Dahlia; Hanum, Fauzia; Nurrohmawati, Lisna; Roslan, Marini Fania; Prihantoro, C. Rudy (Jurnal Pendidikan Teknik dan Vokasional, 2022)
Vocational High School is a vocational education unit at the secondary education level which aims to prepare students to be able to work, either independently or fill existing job vacancies as middle-level workers in accordance with their competencies. One of what makes Vocational High School independent is the teaching factory in it. Destination this research is to analyze implementation of the teaching factory in the world of vocational education using the literature study method. The results show that the teaching factory able to improve the competence of graduates, the implementation of Teaching Factory in Vocational High School can be measured based on the 7x7 Parameter Assessment for Implementation of Teaching Factory. Teaching Factory is a combination of competency-based learning and -based learning production and applied based on actual work procedures and standards for produce products according to the market.